Potentiated zinc and monovalent copper oxide as dietary supplements for weanling piglets: effects on systemic and mucosal immunity, gut permeability, and fecal microbiota composition - Marchetti, Luca; Rebucci, Raffaella; Cremonesi, Paola; Biscarini, Filippo; Castiglioni, Bianca; Lanzoni, Davide; Monteiro, Alessandra; Manaig, Yron Joseph Yabut; Bontempo, Valentino (Frontiers in Veterinary Science, 2026)
This study examines the potential of modulating gut health parameters in piglets by varying zinc/copper ratios administered through specialty oxide sources. A total of 84 piglets were selected after weaning and divided into four experimental treatment groups; the trial lasted 28 days. During the initial phase (1–14 d), the positive control (PC) received 2500 ppm of zinc, provided as conventional zinc oxide. In parallel, three additional treatment groups were formed, in which copper (Cu) and zinc (Zn) were supplemented using potentiated zinc oxide (Pot-ZnO) and monovalent copper oxide (Cu2O), at both European and Non-European recommended inclusion levels: EU (120 ppm of Zn; 140 ppm of Cu), Non-EU+ (300 ppm of Zn; 200 ppm of Cu), and Non-EU− (300 ppm of Zn; 140 ppm of Cu). Lower Zn/Cu ratios characterized the second phase (15–28 d). Growth performance and fecal score were monitored throughout the trial. Blood samples were collected on days 1 and 14 from one subject per replicate to assess serum proinflammatory cytokines, immunoglobulins, and biomarkers of intestinal permeability. On day 28, one subject per replicate was slaughtered to obtain jejunal mucosa for the determination of jejunal secretory immunoglobulin A (sIgA) and alkaline phosphatase. Fecal samples collected on days 14 and 28 were used to analyze Zn and Cu content and to evaluate microbiota composition. A better fecal score was detected on day 4 in PC group compared to EU (p < 0.01). Serum immunoglobulin A increased in Non-EU− vs. PC group (p < 0.05) at day 14. Serum diamine oxidase decreased in the PC and Non-EU+ groups vs. Non-EU− group (p < 0.05) at day 14. sIgA increased in PC vs. Non-EU− group (p < 0.01) at day 28. Zn was higher in PC fecal samples (p < 0.01), whereas fecal Cu increased in EU and Non-EU+ treatments at day 14 (p < 0.05). Analysis of fecal microbiota performed at day 14 showed decreased. Observed, Shannon, and Simpson metrics in the Non-EU− group compared to the EU group (p < 0.05). Beta diversity highlighted a significant separation among groups at day 14 (p < 0.01). Differential abundance analysis revealed notable changes in genera composition among PC and EU groups at day 14 (p < 0.05). In conclusion, balanced Pot-ZnO and Cu2O administered at inclusion levels compliant with European levels of inclusion (EU) represent a valid strategy to enhance gut health of piglets during the first two weeks after weaning.